2005
DOI: 10.1007/s11886-005-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis and management of postoperative atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia seen after cardiac surgery. It is associated with prolongation of hospital stay, postoperative complications, stroke, mortality, and increased hospital cost. Several prevention strategies have been proven effective in reducing postoperative AF; in addition, active prevention of postoperative AF is associated with a decrease in the length of hospital stay and a reduction trend in hospital costs. In patients with postoperative AF, restoration and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Statistics . Assuming a 40% frequency of occurrence of an end‐point arrhythmia after placebo, 2 , 5 , 6 , 7 , 8 a 20% frequency of occurrence after propafenone, and a dropout rate of 20%, and using α = 0.05 and β = 0.20 (power of 80%), a required sample size of ~120 in each group was calculated (two‐sided Fisher's exact test). In order to examine the association between CYP2D6 polymorphism and the efficacy of propafenone, the PM and IM groups were combined, as the numbers of PMs and IMs were small.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics . Assuming a 40% frequency of occurrence of an end‐point arrhythmia after placebo, 2 , 5 , 6 , 7 , 8 a 20% frequency of occurrence after propafenone, and a dropout rate of 20%, and using α = 0.05 and β = 0.20 (power of 80%), a required sample size of ~120 in each group was calculated (two‐sided Fisher's exact test). In order to examine the association between CYP2D6 polymorphism and the efficacy of propafenone, the PM and IM groups were combined, as the numbers of PMs and IMs were small.…”
Section: Methodsmentioning
confidence: 99%
“…Patients undergoing CABG alone have a lower incidence of postoperative atrial fibrillation (25%) than those undergoing valve surgery (35%) or combined CABG‐valve operations (45–60%) 2 . Postoperative atrial fibrillation and other atrial tachyarrhythmias are associated with prolongation of hospital stay, postoperative complications, stroke, mortality, and higher hospital costs as compared with patients who do not develop arrhythmias 2 , 3 , 4 , 5 …”
mentioning
confidence: 99%
“…Beta-blockers enhance ventricular filling, lengthen duration of diastole, decrease atrial pressure and dilatation, reduce atrial ischemia and fibrosis and thereby may improve stretch related arrhythmogenic mechanisms (39). Consistent with this data, beta-blockers have been shown to be effective in prevention of postoperative AF, in adrenergically mediated AF, and in reducing relapse rates of AF following cardioversion (40)(41)(42). BD patients have been found to have increased sympathetic and decreased parasympathetic modulation (43).…”
Section: Discussionmentioning
confidence: 59%
“…7 Magnesium is a cofactor with the sodium-potassium adenosine triphosphatase, which plays a role in myocardial transmembrane function. 20 This regulates the sodium/potassium gradients; therefore, magnesium should be monitored and regulated with the same urgency as potassium.…”
Section: Low-dose Amiodarone and Magnesiummentioning
confidence: 99%
“…The authors concluded that preoperative magnesium was helpful in preventing POAF. 7 Therefore, the combination of magnesium and amiodarone seems to reduce the incidence of POAF. This needs further research as well.…”
Section: Low-dose Amiodarone and Magnesiummentioning
confidence: 99%